Characterization of grass carp CD40 and CD154 genes and the association between their polymorphisms and resistance to grass carp reovirus. Issue 81 (October 2018) - Lu, Xiao-Bing; Chen, Ya-Xin; Cui, Zheng-Wei; Zhang, Xiang-Yang; Lu, Long-Feng; Li, Shun; Xia, Xiao-Qin; Nie, Pin; Zhang, Yong-An
Abstract: In bony fish, CD40 and CD154 are two very important costimulatory molecules involved in T and B cell cooperation in thymus-dependent antibody production. In the current study, we identified the cDNAs of CD40 and CD154 and analyzed their genomic structures in grass carp. Quantitative real-time PCR indicated that the CD40 and CD154 were mainly expressed in immune organs. After challenge with grass carp reovirus (GCRV), these two genes were up-regulated at 72 h in head kidney and spleen. Moreover, seven and five single nucleotide polymorphisms (SNPs) were identified in the CD40 and CD154 respectively. Statistical analysis indicated that three SNPs in the coding region of the CD40 were significantly associated with the resistance of grass carp against GCRV. These results indicated that CD40 and CD154 play important roles in the responses to GCRV in grass carp. The SNP markers in the CD40 associated with the resistance to GCRV may facilitate the disease-resistant breeding of grass carp. Highlights: CD40 and CD154 are two important costimulatory molecules in adaptive immunity. CD40 and CD154 genes were cloned and characterized in grass carp. Seven and five SNP loci were respectively identified in grass carp CD40 and CD154. Three SNP loci in the intracellular domain-encoding region of CD40 were associated with resistance to GCRV.